Superlative syntactic amalgams in an Iberian Spanish dialect - Sáez del Álamo, Luis Ángel (Borealis – An International Journal of Hispanic Linguistics, 2020)
This article addresses an as yet unnoticed Spanish superlative construction attested in the mid area of Northern Spain. This construction features two striking properties: (i) it contains a relative pronoun which, at first glance, does not seem to introduce a TP (there is no overt verb to its right), which raises the question how the relative pronoun can obtain its Case/theta role; (ii) even if it were true that the relative pronoun actually introduces a TP and heads a full subordinate clause (presumably a free relative), the latter would arise in an anomalous position which disrupts the natural word order of the main clause and where it seems to lack any obvious licensor (as an adjunct, argument or predicate). A simultaneous answer to both problems will be obtained from the proposal that the construction at issue is a “syntactic amalgam” (Lakoff 1974): (i) assuming Kluck’s (2011) approach to amalgams, the relative pronoun of the construction can unproblematically be considered to introduce a sluiced TP, so it heads a full relative clause and does have a (covert) Case/theta-role licensor; (ii) the disruptive position of the relative clause and the opacity for licensing from the main clause are now expected as they are the defining properties of the so-called “interrupting clauses” in Horn-/Andrews-amalgams. As in Kluck (2011), such properties will be assumed to result from the operation “par-merge” giving rise to paratactical configurations (de Vries 2007).